KEKUATAN PEMBUKTIAN SAKSI DAN SALINAN TULISAN DALAM SENGKETA KEPEMILIKAN TANAH DALAM PERSPEKTIF HUKUM ACARA PERDATA INDONESIA - Paembonan, Chandra Putra Toban; T. Vaison Siahaan; Rospita Adelina Siregar (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The law of evidence is a set of rules and regulation that must be followed by The Judge during the court process in making a decision for justice seeker. The status in the law of evidence is not only found in Formal Law (Procedure Law), but also in Material Law. It can be interpreted that The Law of Evidence in the classification of Material Law is to guarantee the application of the Material Law itself in the court process. The impact of The Law of Evidence is to find justice, since The Judge may consider the decision to a case with the evidence tools proposed by both sides. In this research, the writer uses a normative research method in which the writer uses the primary and secondary objects. Besides that, the writer also uses the empirical research method in which the writer obtains the information by interviewing the informants. Next, the writer analyses and makes conclusion based on the case researched by the writer. The purpose of the study is to acquaint the power of The Judge in deciding the case based on the evidence using the duplicate paper (photo copy) and witness's tools (testimonium de auditu). In writing this research, the writer obtains the conclusion of the power of The Judge in deciding a case using the evidence of duplicate paper (photo copy) even without the original paper and using witness's tools-testimonium de audito.